1998
DOI: 10.1056/nejm199811193392101
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Alfa-2b Alone or in Combination with Ribavirin as Initial Treatment for Chronic Hepatitis C

Abstract: In patients with chronic hepatitis C, initial therapy with interferon and ribavirin was more effective than treatment with interferon alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

89
2,421
16
65

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,232 publications
(2,591 citation statements)
references
References 33 publications
89
2,421
16
65
Order By: Relevance
“…While this activity is not deleterious to most human cells, erythrocytes (RBCs) are adversely affected [2][3][4], and the vast majority of subjects receiving RBV become anemic [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…While this activity is not deleterious to most human cells, erythrocytes (RBCs) are adversely affected [2][3][4], and the vast majority of subjects receiving RBV become anemic [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Across six phase 3 studies of OBV/PTV/r + DSV + RBV, RBV dose reductions were required in only 6.5% of patients, compared with approximately 20% of patients receiving pegIFN/RBV therapy in past studies 1, 2. Head‐to‐head studies have recently reported RBV dose reductions to be lower in patients receiving OBV/PTV/r + DSV + RBV compared with those receiving the first‐generation protease inhibitor, telaprevir, in combination with pegIFN/RBV 17…”
Section: Discussionmentioning
confidence: 99%
“…In combination with standard interferon and pegylated interferon (pegIFN), ribavirin (RBV) has been shown to significantly decrease the risk of post‐treatment viral relapse and increase rates of sustained virological response (SVR) in patients with hepatitis C virus (HCV) infection 1, 2. Despite improving the efficacy of IFN‐based therapy, RBV is associated with haemolytic anaemia,3, 4 a phenomenon driven by accumulation of RBV in erythrocytes and oxidative damage within the red blood cells 5.…”
Section: Introductionmentioning
confidence: 99%
“…Ribavirin is a mutagen and inhibitor of viral RNA polymerase. 13,14 It shows antiviral activity against a variety of RNA viruses and is used to treat infections of hepatitis C virus in combination with interferon-a 15,16 and of lassa fever virus. 17 The method of using antiviral drugs might offer a novel approach for regulated SeV-mediated gene expression in primate ES cells.…”
Section: Introductionmentioning
confidence: 99%